Chronic urticaria in a two year old child: a diagnostic dilemma - Suresh, Jayasurya; R., Nidheesh Chandran (International Journal of Contemporary Pediatrics, 2020)
A 2 year old child presented with history of recurrent urticaria for 2 months. The cause was initially idiopathic. On close questioning about diet and observation it was found that mother started using a coriander based masala powder 2 months back and it was found that the child was allergic to coriander. Chronic urticaria should be dealt with extreme caution and careful elicitation of history for the offending agent should be taken in a case of urticaria which poses as a diagnostic dilemma.